Learning from Northern clingfish (Gobiesox maeandricus): bioinspired suction cups attach to rough surfaces. (28th October 2019) - Ditsche, Petra; Summers, Adam
Abstract : While artificial suction cups only attach well to smooth surfaces, the Northern clingfish can attach to surfaces ranging from nanoscale smooth to rough stone. This ability is highly desirable for technical applications. The morphology of the fish's suction disc and its ability to attach to rough and slimy surfaces have been described before, and here we aim to close gaps in the biomechanical understanding, and transfer the biomechanical principles to technical suction cups. We demonstrate that the margin of the suction disc is the critical feature enabling attachment to rough surfaces. Second, friction measurements show that friction of the disc rim is increased on rough substrates and contributes to high tenacity. Increased friction causes a delay in failure of the suction cup and increases the attachment force. We were able to implement these concepts to develop the first suction cups bioinspired by Northern clingfish. These cups attach with tenacities up to 70 kPa on surfaces as rough as 270 µm grain size. The application of this technology is promising in fields such as surgery, industrial production processes and whale tagging. This article is part of the theme issue 'Transdisciplinary approaches to the study of adhesion and adhesives in biological systems'.